Comparative study of linear co-volume based mixing rules for equation of state/ excess GIBBS energy (EOS/GE) models for CO2 â MEA and CO2 â MDEA systems - Suleman, H. (Trans Tech Publications Ltd, 2014)
With the advent of Equation of State/ Excess Gibbs Energy (EOS/GE) models, the linear co-volume based mixing rules have gained vast importance for predicting multi-component VLE for polar mixtures. Owing to their inherent ease of calculation and good prediction abilities, these mixing rules have been applied in extension, to a variety of systems especially for CO2-H2Oalkanolamine systems. However, no comparative study is available to select appropriate mixing rule for prediction of thermodynamic properties. In this study, pressure prediction of various linear covolume mixing rules has been compared for CO2 â MEA and CO2 â MDEA systems, while effects of activity coefficients and process parameters have been kept constant. The infinite pressure mixing rules have heavily under â predicted and approximate zero reference pressure mixing rules have over â predicted, but latter are valid for low and medium pressure ranges. The linear combination of Vidal and Michelsen (LCVM) mixing rule have good predictions at high pressures. Â© 2014 Trans Tech Publications, Switzerland.